Golay Code Excitation of Ultrasonic Transducers with Different Backing - Wojciech SECOMSKI; Ihor TROTS; Andrzej NOWICKI (Archives of Acoustics, 2008)
Two 3.7 MHz focused ultrasonic transducers were built. One without backing and the second loaded on back. The primary application of the first transducer is Doppler blood flow measuring ultrasonic devices, the second is most useful for the B-mode imaging devices. The electrical and acoustical properties were tested and finally the results of the different Golay code excitations were compared. Efficiency of the not backed transducer was 4.1 dB higher. The not backed transducer performed maximum sensitivity for 8 bit two periods per bit code excitation. The backed transducer achieved maximum axial resolution for 16 bit one period per bit excitation.